Experimental comparison of Yb/Al/Ce and Yb/Al/P co-doped fibers on the suppression of transverse mode instability - Zhang, Zhilun; Luo, Yonghui; Xing, Yingbin; Li, Haiqing; Peng, Jinggang; Dai, Nengli; Li, Jinyan (Frontiers in Physics, 2023)
We presented an experimental comparison of the core-composition difference on the suppression of the photodarkening (PD) and transverse mode instability (TMI) effects. Two core-composition fibers, entailing Yb/Al/Ce and Yb/Al/P co-doped fibers, were fabricated by MCVD process combined with solution doping technique. The parameters of two fibers were almost the same. The PD-induced loss at equilibrium was 3.94 dB/m at 702 nm in Yb/Al/Ce fiber, while it was 0.99 dB/m in Yb/Al/P fiber. To obtain a deeper understanding of the impact of PD on laser performance, a bidirectional pumping fiber amplifier was constructed. Compared with Yb/Al/Ce co-doped fiber, the TMI thresholds of Yb/Al/P co-doped fiber were enhanced in co-pumped and counter-pumped schemes. Meanwhile, the slope efficiency in bidirectional scheme was promoted by 4%. Moreover, the transmittance at 638 nm confirmed the superior PD resistance of Yb/Al/P co-doped fiber. These experimental results pave the way for the further development of high-power fiber lasers.